The Q-Time Deformed Wave Equation. (6th May 2022) - Al-Hossain Ahmad, Al-Nashri; Altoum, Sami H.
Abstract : For q ∈ 0, 1, we introduce the q -time deformed wave equation; using the q -derivative, the solution of the q -time deformed wave equation is given. Also, we introduce the free-time wave equation which is a limit case q ⟶ 0 of the q -time deformed wave equation.